Primary Immunodeficiencies Associated With Early-Onset Inflammatory Bowel Disease in Southeast and East Asia - Sasahara, Yoji; Uchida, Takashi; Suzuki, Tasuku; Abukawa, Daiki (Frontiers in Immunology, 2022)
Background: Causes of early-onset inflammatory bowel disease (IBD) vary, and primary immunodeficiency diseases (PIDs) are associated with early-onset IBD as monogenic disorders. Aim: This review investigates the prevalence, clinical manifestation, genetic profile, and treatment of patients with early-onset IBD in Southeast and East Asia. Methods: A systemic review of articles reporting PID patients associated with early-onset IBD in Southeast and East Asia was conducted. Results: The prevalence of PID associated with IBD was higher than that reported in western nations, and the frequency of patients with bloody stools as an early symptom was relatively higher in monogenic diseases. A total 13 (12.0%) of 108 patients with early-onset IBD were diagnosed as PID by exome sequencing and targeted gene panel analysis in Japan, including four patients with XIAP, three with IL10RA, and two or one patient with other gene mutations. In addition, ten patients were reported as having IL-10 receptor alpha (IL-10RA) deficiency in China and Hong Kong. Allogeneic hematopoietic stem cell transplantation was performed in patients with X-linked inhibitor of apoptosis deficiency, IL-10RA deficiency, or other PID as a curative treatment, and the preferable outcome of reduced-intensity conditioning and complete resolution of IBD symptoms and dysbiosis were achieved. 　　　　 Conclusion: Comprehensive molecular diagnosis has been widely applied to screen for patients with PID-associated IBD in Southeast and East Asia. These results contributed to the awareness of monogenic PID in early-onset IBD patients and their differences in clinical manifestations and genetic profiles compared to the patients in western counties.